Pengaruh Promosi Sosial Media dan Store Atmosphere Terhadap Keputusan Pembelian di Kafe Shan Juice Karawang Tahun 2022 - Kartika Sukmawati Dewi; H. Cecep Hermana (Peneliti.net, 2023)
The development of the business world, especially in the culinary field, has triggered the emergence of new entrepreneurs. The culinary business is quite a promising business because it deals with basic human needs. The emergence of a variety of unique foods, the existence of culinary tours, and culinary trends as a lifestyle for the community, is proof that this business is growing rapidly. Karawang district has now become a driver of demand for the food and beverage industry which is quite large. This condition has become a special attraction for local and foreign entrepreneurs to try their luck in the midst of increasingly competitive competition. One of the developments that occurred in Karawang district is the presence of large shopping centers, hotels and many restaurants and cafes. Therefore the authors feel interested in conducting research related to Social Media Promotion and Store Atmosphere can influence purchasing decisions. The research that the writer will do is contained in this thesis entitled The Effect of Social Media Promotion and Store Atmosphere on Purchasing Decisions at the Shan Juice Karawang Cafe in 2022.